Attachment measures in middle childhood and adolescence: A systematic review of measurement properties. (March 2019) - Jewell, Tom; Gardner, Tessa; Susi, Karima; Watchorn, Kate; Coopey, Emily; Simic, Mima; Fonagy, Peter; Eisler, Ivan
Abstract: Background: Attachment theory proposes that humans develop representations of self and other in early childhood which are relatively stable across the life-course, and play a key role in psychological adaptation. However, to date, the psychometric properties of attachment measures in middle childhood and adolescence have not been evaluated in a systematic review. Method: A systematic review (PROSPERO ID: CRD42017057772) was conducted using COSMIN criteria. Two researchers independently searched MEDLINE, PsychINFO and Embase databases for relevant articles. Results: Fifty-four studies were included in the review. The methodological quality of studies was typically fair or poor, with only a small number of studies being rated as of good or excellent quality. The measurement properties of attachment measures in this age group were frequently rated as inadequate according to COSMIN criteria. The Child Attachment Interview (CAI) has the best psychometric properties of the interview and projective measures, and the Inventory of Parent and Peer Attachment (IPPA) the best evidence of the self-report measures. Overall, the evidence for the CAI and IPPA included both positive and negative findings relating to adequacy of measurement properties. Conclusions: Attachment measures in middle childhood and adolescence currently have limited evidence for the adequacy of their psychometric properties. Highlights: Attachment insecurity is known to be a risk factor and correlate of psychopathology. This review is the first to systematically appraise the psychometric properties of all attachment measures in middle childhood and adolescence. Only a small number of attachment measures developed for middle childhood and adolescence have adequate measurement properties. Interview and projective measures of attachment should be used cautiously in clinical practice. Our findings converge with evidence from both infancy and adulthood in pointing to the underlying structure of attachment as being dimensional.